L’io come "albergo a ore". Il sogetto adattativo nell’opera di Gabriele Frasca - Policastro, Gilda (L’ospite ingrato, 2022)
The essay aims to investigate the questioning of the subject in Gabriele Frasca’s work, especially in his poetic work, but with reference to concepts theorized in his non-fiction writing. On the one hand, the reaction to the predominance of the ego in the adoption of closed forms (“reopened”, however, at each new use) at the beginning of his production; on the other hand, the presence (constant throughout his work) of an “I” that does not respond to the instances of intimist (and bourgeois) subjectivity but rather to the need to identify a common essence in the biological root, in finitude, in the “remaking” (biologically, to be precise) of verses, in a sort of compromise between pose and life, finitude and creative turmoil. A creation where the voice, the listening, the diction of poetry becomes a megaphone and not as an introverted whisper.